Optimizing Recognition and Management of Patients at Risk for Infection-Related Decompensation Through Team-Based Decision Making. Issue 2 (30th March 2023) - Martinez, Elizabeth M.; Sepanski, Robert J.; Jennings, A. Dawn; Schmidt, James M.; Cholis, Thomas J.; Dominy, Meaghan E.; Devlin, Sanaz B.; Eilers, Lindsay Floyd; Zaritsky, Arno L.; Godambe, Sandip A.
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Introduction: Pediatric sepsis is a leading cause of death among children. Electronic alert systems may improve early recognition but do not consistently result in timely interventions given the multitude of clinical presentations, lack of treatment consensus, standardized order sets, and inadequate interdisciplinary team-based communication. We conducted a quality improvement project to improve timely critical treatment of patients at risk for infection-related decompensation (IRD) through team-based communication and standardized treatment workflow. Methods: We evaluated children at risk for IRD as evidenced by the activation of an electronic alert system (Children at High Risk Alert Tool [CAHR-AT]) in the emergency department. Outcomes were assessed after multiple improvements including CAHR-AT implementation, clinical coassessment, visual cues for situational awareness, huddles, and standardized order sets. Results: With visual cue activation, initial huddle compliance increased from 7.8% to 65.3% ( p < .001). Children receiving antibiotics by 3 hours postactivation increased from 37.9% pre–CAHR-AT to 50.7% posthuddle implementation ( p < .0001); patients who received a fluid bolus by 3 hours post-CAHR activation increased from 49.0% to 55.2% ( p = .001). Conclusions: Implementing a well-validated electronic alert tool did not improve quality measures of timely treatment for high-risk patients until combined with team-based communication, standardized reassessment, and treatment workflow.